Consistency between parameterisations of aerosol hygroscopicity and CCN activity during the RHaMBLe discovery cruise - N. Good; D. O. Topping; J. D. Allan; M. Flynn; E. Fuentes; M. Irwin; P. I. Williams; H. Coe; G. McFiggans (Atmospheric Chemistry and Physics, 2010)
Results from a measurement study performed in the Tropical Atlantic on board the RHaMBLe Discovery Cruise D319 are presented. Measurements of aerosol composition, hygroscopicity and CCN activity were used to test the ability of a single parameter model to describe water uptake in sub- and supersaturated conditions. It was found that the magnitude and temporal variability of the sub-saturated water uptake could be well represented using the non-refractory composition to derive the model input for 2 periods when the large majority of the aerosol mass was non-refractory. As may be expected, when a significant fraction of the aerosol volume is refractory the sub-saturated water uptake is not well predicted by the non-refractory composition. When predicting the cloud activation potential from the composition and the hygroscopicity there is a consistent under-prediction of the CCN activity. The prediction of CCN activity from the sub-saturated water uptake gives a better prediction of the CCN activity than the composition when the non-refractory components are not fully representative of the aerosol composition. Based on these observations it appears that a single parameter cannot always capture the behavior fully across the sub- and supersaturated regimes. Measurements made at relative humidities (RHs) up to 94% showed that the water activity appears satisfactorily represented by a single parameter derived at 90% RH. It therefore appears that the change in the observed hygroscopicity take place between 94% RH and the point of activation. This change may be due in part to a change solution non-ideality, surface tension effects or the presence of sparingly soluble compounds for example, but cannot be reconciled without measurements at higher RHs.